Heat stress induces proteomic changes in the liver and mammary tissue of dairy cows independent of feed intake: An iTRAQ study - Ma, Lu (PLoS One, 2019)
Heat stress decreases milk yield and deleteriously alters milk composition. Reduced feed intake partially explains some of the consequences of heat stress, but metabolic changes in the mammary tissue and liver associated with milk synthesis have not been thoroughly evaluated. In the current study, changes of protein abundance in the mammary tissue and liver between heat-stressed cows with ad libitum intake and pair-fed thermal neutral cows were investigated using the iTRAQ proteomic approach. Most of the differentially expressed proteins from mammary tissue and liver between heat-stressed and pair-fed cows were involved in Gene Ontology category of protein metabolic process. Pathway analysis indicated that differentially expressed proteins in the mammary tissue were related to pyruvate, glyoxylate and dicarboxylate metabolism pathways, while those in the liver participated in oxidative phosphorylation and antigen processing and presentation pathways. Several heat shock proteins directly interact with each other and were considered as central “hubs” in the protein interaction network. These findings provide new insights to understand the turnover of protein biosynthesis pathways within hepatic and mammary tissue that likely contribute to changes in milk composition from heat-stressed cows.